Recent advance in the development of tuberculosis vaccines in clinical trials and virus-like particle-based vaccine candidates - Zhou, Fangbin; Zhang, Dongmei (Frontiers in Immunology, 2023)
Tuberculosis (TB) remains a serious public health threat around the world. An effective vaccine is urgently required for cost-effective, long-term control of TB. However, the only licensed vaccine Bacillus Calmette-Guerin (BCG) is limited to prevent TB for its highly variable efficacy. Substantial progress has been made in research and development (R&D) of TB vaccines in the past decades, and a dozen vaccine candidates, including live attenuated mycobacterial vaccines, killed mycobacterial vaccines, adjuvanted subunit vaccines, viral vector vaccines, and messenger RNA (mRNA) vaccines were developed in clinical trials to date. Nevertheless, many challenges to the successful authorization for the use and deployment of an effective tuberculosis vaccine remain. Therefore, it is still necessary and urgent to continue exploring new vaccine construction approaches. Virus-like particles (VLPs) present excellent prospects in the field of vaccine development because of their helpful immunological features such as being safe templates without containing viral nucleic acid, repetitive surface geometry, conformational epitopes similar to natural viruses, and enhancing both innate and adaptive immune responses. The marketization process of VLP vaccines has never stopped despite VLP vaccines face several shortcomings such as their complex and slow development process and high production cost, and several VLP-based vaccines, including vaccines against Human papillomavirus (HPV), Hepatitis B Virus (HBV) and malaria, are successfully licensed for use at the market. In this review, we provide an update on the current progress regarding the development of TB vaccines in clinical trials and seek to give an overview of VLP-based TB vaccine candidates.